IMPLEMENTATION OF STAD MODEL IN THE WRITING OF BEST PRACTICE AT MGMP INDONESIAN MTS LEVEL PADANG CITY - Dina Fitria Handayani; Lisa Yuniarti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2023)
Teachers have an obligation to develop the profession in a sustainable manner. Scientific publication is one way to do this. One type of scientific publication that has a credit score of 2 points and is recommended for teacher promotion is best practice. Best practice is a paper that tell about the best experience of an educator in improving the quality of education and teaching services in schools. This study aims to see how successful the use of the STAD model is in writing best practice scientific papers at the Indonesian Language MGMP MTs Padang City level. This research model is descriptive with a survey approach. This study shows that teachers who have a high understanding of writing best practice scientific papers are 64.3%. Meanwhile, 21.4% had a moderate understanding and the other 14.3% had a low understanding of writing best practice scientific papers. Based on the three percentages above, it shows that more teachers have an understanding of writing best practice scientific papers. Writing published best practices can help teachers fulfill 2 points in promotion. The obstacles faced by teachers when writing best practices lie in time, other tasks outside the teaching profession, and determining the best experience that has been passed by the teacher. The use of the STAD model makes it easier for teachers to develop and foster cooperative, critical, and creative thinking that can help make collaborative learning easier